Prucalopride inhibits the glioma cells proliferation and induces autophagy via AKT-mTOR pathway - Hong Qiao (BMC Neurology, 2018)
Abstract Backgrounds Glioma is the most fatal primary brain glioma in central nervous system mainly attributed to its high invasion. Prucalopride, a Serotonin-4 (5-HT4) receptor agonist, has been reported to regulate neurodevelopment. This study aimed to investigate the influence of the Prucalopride on glioma cells and unveil underlying mechanism. Methods In this study, glioma cells proliferation was evaluated by Cell counting kit-8 (CCK8). Wound healing and transwell assay were used to test cellular migration and invasion. Flow cytometry was utilized to determine cellular apoptosis rate. Apoptosis related markers, autophagy markers, and protein kinase B (AKT)-mammalian target of rapamycin (mTOR) pathway key molecules were detected using western blot assay. Results As a result, the proliferation, migration and invasiveness of glioma cells were impaired by Prucalopride treatment, the apoptosis rate of glioma cells was enhanced by Prucalopride stimulation, accompanied by the increased pro-apoptosis proteins Bax and Cleaved caspase-3 and decreased anti-apoptosis protein Bcl-2. Prucalopride significantly promoted autophagy by increased expression level of Beclin 1 and LC3-II, while decreased expression level of p62. Prucalopride administration resulted in obvious inhibitions of key molecules of AKT-mTOR pathway, including phosphorylated- (p-) AKT, p-mTOR and phosphorylated-ribosomal p70S6 kinase (p-P70S6K). Conclusions Taking together, these results indicate that Prucalopride may be likely to play an anti-tumor role in glioma cells, which suggests potential implications for glioma promising therapy alternation in the further clinics.